Women's experiences of infertility – towards a relational model of care. Issue 23 (8th October 2013) - Cunningham, Nicola; Cunningham, Tom
Abstract : Aims and objectives: To consider the effectiveness of current models of patient‐centred infertility care. Background: Patient centredness is defined as one of six key dimensions of quality of care. In the field of infertility, a new interaction model of patient‐centred infertility care is proposed. Despite positive moves, this model reveals shortcomings in knowledge about the lived experience of infertility and lacks the shift in attitudes and approach that effective patient‐centred care requires. Design: The study has a qualitative research design. Nine women living with and through infertility participated in online life‐story interviews. Methods: Data were analysed using a layered strategy influenced by the voice‐centred relational method, emphasising narrative content, form and function. Results: Women reveal a complex experience. Three key themes were found: Approaching the clinic narratives are infused with personal expectations while deeply reflective of cultural expectations and social norms. Relatedness recognises women's experiences cannot be neatly separated into distinct domains. Liminality and infertility describes women's experiences lost in transition through and beyond infertility treatment. Conclusions: The current model of patient‐centred infertility care requires further development. Women in this study found themselves lost in transition and irrespective of treatment failure or success. Conceptual development must embrace a relational understanding of patient's experience to ensure that patient‐centred infertility care is realistic and relevant to patients, clinical staff and the system as a whole. Relevance to clinical practice: Psychosocial skills are recognised as core competences for fertility nurses. A relational conceptualisation of patient's experiences, living with and through infertility, provides further information for the development of staff and enhanced knowledge and practice skills.